Փոխգնդապետի շիրմաքարը - Հարությունյան, Ա. Ա.
Автором показано, что против Имама Шамиля в рялах царской армии воевал не только Иван Аазарьев, но и лругой уроженец горола Шуши - полполковник Исаи Иванович Грамов. Он, как свилетельствует налгребная налпись на его могиле, разбил Шамиля и освоболил из плена семью грузинского князя Орбеля Чавчавалзе. The author proves that in the tsar army fighting against Imam Shamil there served not only Ivan Lazariev but also another native of Shushi town lieutenant -colonel Isaiah Ivanovich Gramoff. He as it is evident from the inscription on his gravestone routed Shamil and rescued from captivity the family of Georgian Prince Orbel Chavchavadze.
Keywords: Պատմություն; Շուշի